Urinary tract infections: raising problem in developing countries. Issue 4 (October 2018) - Shiralizadeh, Somayeh; Taghizadeh, Sepehr; Asgharzadeh, Mohammad; Shokouhi, Behrooz; Gholizadeh, Pourya; Rahbar, Mohammad; Samadi Kafil, Hossein
Abstract : N/A: Urinary tract infections are the most common infections worldwide, which can involve the urethra, bladder and kidney and are caused by Gram-negative bacteria, followed by Gram-positive bacteria or fungi. Escherichia coli and Klebsiella species are the most common uropathogens. Misuse of antibiotics and passage of resistance genes between uropathogens play main role in increasing drug resistance. Increase of multidrug resistance and emergence of extended-spectrum beta-lactamases among uropathogens are concerned worldwide. Antimicrobial resistance patterns vary from time-to-time and across different regions. Hence, treatments must be conducted according to local prevalence of causative uropathogens, risk factors for multidrug-resistance and antimicrobial-resistance patterns of bacterial strains. This review discusses urinary tract infections in developing countries, including their mechanisms and risk factors.